The race for best friendship in Sino-Gulf relations: fractured cooperation and conflict in times of strategic uncertainty - Thies, Antonia; Zumbraegel, Tobias; Demmelhuber, Thomas (International Relations, 2025)
The scholarly debate on a changing Gulf monarchies’ role in international politics has been vividly evolving throughout the last years. It was particularly nurtured by an assumed waning US hegemony in the region and thriving Belt and Road Initiatives of China since 2013. Contributions on the state of Sino-Gulf relations got a massive booster in view of COVID19 since China had presented itself as the most reliable partner with sufficient knowledge and expertise to fight the pandemic. This article is based on the argument that the Gulf monarchies (in our sample: Saudi Arabia, the United Arab Emirates, and Qatar) adjust their foreign policies toward this key player in the Indo-Pacific in order to prepare themselves for strategic uncertainties and security risks on a domestic, regional, and international level. By relying on the expanded IR concept of hedging, we present evidence how this leads to frictions and tensions on the regional level among the Gulf monarchies that have long been described as a like-minded club of authoritarian monarchie